Comparison of the turn switch time points measured by portable force platforms and pressure insoles - Martinez Álvarez, A.; Nakazato, K.; Scheiber, P.; Snyder, C.; Stöggl, T. L. (Frontiers in Sports and Active Living, 2020)
Several methods to determine turn switch points during alpine skiing using the vertical GRF exist in the literature. Although comparative studies between pressure insoles (PI) and force platforms (FP) have been conducted, there are no reports comparing the detected time points. Yet, these sensors and methods have been used interchangeably. This study aims to compare the turn switch time points with both sensors and various methods. 20 skiers performed turns with FP and PI for two different ski styles (high and low dynamic turns). Three different assessment methodologies were compared: minima, functional minima and crossings. Bland Altman and repeated measures ANOVA were used to assess statistical differences. Main effects of sensor and method were observed (p<0.001). Although there was a low effect size (pEta2 = 0.013) between FP and PI, the 95% CI yielded values representing >30% of the turn duration. A large effect size (Eta2 = 0.153) was found between the crossing method and the minima and functional minima methods. This indicates that those methods assess different events during the turn switch phase. In conclusion, the sensors and assessment methodologies compared in this study are not interchangeable with the possible exception of the minima and functional minima assessed with FP.